Effects of Organophosphate Pesticides on Neurological Impairment - Thammachai, Ajchamon; Sapbamrer, Ratana (Naresuan University Journal: Science and Technology (NUJST); Vol 29 No 1 (2021): January - March 2021DO - 10.14456/nujst.2021.1, 2020)
Exposure to organophosphate pesticides (OPs) was found to be associated with an increasing prevalence of neurological symptoms, neuropsychological function and involved in postural balance. However, available scientific data is limited. Therefore, the aim of this article was to review scientific evidence published on the effects of OPs on neurological impairment. The topics presented in the article are as follows: 1) organophosphate pesticide use and exposure, 2) mechanism of OPs toxicity on the neurological system 3) tools for assessment of the neurological system 4) effect of exposure to OPs on neurological signs 5) effect of exposure to OPs on neuropsychological functioning and 6) effect of exposure to OPs on postural balance. Considerable evidence suggests that electrophysiological changes include abnormalities point to remodeling of the motor unit, abnormal small and large nerve fiber function, reduced compound muscle action potential (CMAP) amplitude and ulnar F-wave, abnormal ulnar, tibial, peroneal, and sural nerve conduction. OPs exposure has been implicated in cognitive impairment including deficits of memory, attention, perception and visuospatial function, executive function, language, IQ, and other neuropsychological implications include psychiatric disorders, anxiety, insomnia, major depression, and dementia. A greater postural sway with exposure to OPs than in the unexposed. This article recommends future studies and possibilities for incorporating sensitive health outcomes. The measurement of OPs monitoring on a larger scale is warranted. Keywords: insecticides, neurological impairment, neuropsychological function, organophosphate pesticides, postural balance